Optimized Scheduling Under Master-Slave Game Considering Charging Power Segmental Regulation of Electric Vehicles - TENG Changlong, HU Qinran, JI Zhenya, QIAN Tao, LIANG Yiheng (Dianli jianshe)
[Objective] Electric vehicles （EVs） and distributed resources are crucial for advancing “dual carbon” targets， with microgrid-based aggregated game scheduling representing one of the effective regulation forms. However， existing scheduling strategies mostly overlook the segmented regulation capability of orderly charging， hindering further optimization of charging prices and constraining flexible coordination between charging loads and distributed resources， thereby affecting the overall economic and low-carbon benefits. [Methods] First， we establish a scheduling framework with multi-agent aggregators as the leading entities and EVs as the following entities， formulating dynamic charging prices and aggregators’ electricity selling prices while considering carbon trading. Second， we design a segmented regulation strategy for EV charging power capable of flexibly adjusting the charging power and duration while satisfying the charging requirements of EV users. Finally， to address challenges such as increased equilibrium game variables and decreased computation speed resulting from segmented regulation， we adopt an improved Kriging meta-model for solving， reducing the computational load， and improving the solving efficiency. [Results] The simulation results show that the proposed method reduces charging and aggregation operating costs under the combined effect of the segmented adjustable charging strategy and dynamic charging price. The operating costs of the EV aggregators were reduced by 15.1%； moreover， the load peak-valley difference could also be optimized. Compared with the disorderly charging scenarios， the peak-valley difference rate of the proposed method was reduced by 11.6% while reducing the carbon emissions caused by EV charging. [Conclusions] The flexibility of EV grid connection adjustment was improved by optimizing the charging power through a segmented adjustment. The joint action of EV dynamic charging prices and distributed resource aggregator electricity prices helped realize the low-carbon complementary advantages of EV and different distributed resources， resulting in reduced carbon emissions while achieving good peak shaving and valley filling effects.